2002
DOI: 10.1097/00005373-200205000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet Therapy: An Alternative to Heparin for Blunt Carotid Injury

Abstract: Contrary to previous reports, we did not observe improved outcomes with full anticoagulation compared with antiplatelet therapy. Anticoagulation was associated with increased extracranial bleeding complications. The risks and possible benefits, as well as timing, of anticoagulation or antiplatelet therapy for BCI should be carefully weighed by the major care providers of the patient with multiple injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 23 publications
4
86
0
1
Order By: Relevance
“…Previous study has shown that in even in asymptomatic, untreated patients with BCVI, the rate of neurological complications can be as high as 21.5% 28 . Some authors have recommended the use of antiplatelet agents as an alternative to avoid the hemorrhagic risks associated with systemic heparin 29,30 . Previous studies have documented decreased stroke rate from approximately 30%-50% to 2%-10% using anticoagulation or antiplatelet therapy 4,6,8,17,22,26,31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study has shown that in even in asymptomatic, untreated patients with BCVI, the rate of neurological complications can be as high as 21.5% 28 . Some authors have recommended the use of antiplatelet agents as an alternative to avoid the hemorrhagic risks associated with systemic heparin 29,30 . Previous studies have documented decreased stroke rate from approximately 30%-50% to 2%-10% using anticoagulation or antiplatelet therapy 4,6,8,17,22,26,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented decreased stroke rate from approximately 30%-50% to 2%-10% using anticoagulation or antiplatelet therapy 4,6,8,17,22,26,31 . Although there have been no randomized trials, retrospective analyses suggest that both therapies are equally efficacious in reducing ischemic events 6,8,17,30,32 . It is often not possible to prescribe therapy for BCVI on a protocol basis, and individualized therapy is necessary depending on extent of concurrent injury.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, CTA remains an unproven diagnostic modality for this injury, with a sensitivity of between 50% to 68%. 2,3,25 In particular, injuries that may be missed by such noninvasive studies are typically grade I and II injuries; however, pseudoaneurysms and occlusions have also been misdiagnosed. 2,3 The risk associated with angiography in our screened trauma population was 0.1%, while the stroke risk for an undiagnosed grade I CAI is 8% and of VAI is 6%.…”
Section: Diagnostic Imaging and Injury Grading Scalementioning
confidence: 99%
“…5,7,8,16,19,26 Whereas our earlier reports explored blunt vertebral artery injuries (BVIs), this current report presents our evaluation of Grade 1 and 2 BCIs. Imaging, progression of injury, and outcomes of these lower-grade BCIs were analyzed to abbreviatioNs ASA = acetylsalicylic acid; BCI = blunt carotid artery injury; BCVI = blunt cerebrovascular injury; BVI = blunt vertebral artery injury; CTA = CT angiography; DSA = digital subtraction angiography; MVC = motor vehicle collision.…”
mentioning
confidence: 99%